A diversidade de mecanismos de governança na multiplicação de sementes de milho híbrido e soja no Brasil - Feltre, Cristiane (Universidade Federal de São Carlos, 2005)
The coexistence of different mechanisms of governance for similar transactions is a major feature of the seed sector, particularly in the branches of soybeans and hybrid corn. Also, the procurement of different inputs is governed by similar governance structures. Both seed sectors are characterized by high investments in research and development and are subjected to several hazards and uncertainty. One of the main determinants of competitiveness in this industry is the quality of the inputs that will be launched in the market. As a consequence, the activities of research, development and reproduction of seeds are crucial in the competition, requiring need high level of control. In spite of this, the firms that develop high technology seeds present different arrangements in the organization of the production of inputs. The reproduction of seeds requires some mechanisms in order to fully appropriate of the benefits of innovation. This fact constitutes an important determinant of choice for these different arrangements. This dissertation aims to analyze the determinants of the boundaries of the firms, and how the selected governance structures interact with the firm s strategies. This dissertation also aims to explore the different appropriability mechanisms that are available to this sector, in each of its main segments hybrid and varieties. The dissertation uses Transaction Cost Economics, and Dynamic Capabilities as its main theoretical background. Also, the governance inseparability concept gave support to the questions associated to contractual relations. The empirical research, focused on large firms that undertake R&D activities, concludes the factors that influence in the decisions about the reproduction of seeds are related to transaction cost reasoning, but to dynamic capabilities and governance inseparability arguments as well.
Keywords: Organização industrial; Sementes - indústria; Custos de transação; Competências dinâmicas; Seed Industry; Transaction Cost Economics; Dynamic Capabilities; Innovation Appropriability; CIENCIAS SOCIAIS APLICADAS::ECONOMIA